Neural Correlates of Cognitive Dysfunctions in Cervical Spondylotic Myelopathy Patients: A Resting-State fMRI Study - Zhao, Rui; Su, Qian; Chen, Zhao; Sun, Haoran; Liang, Meng; Xue, Yuan (Frontiers in Neurology, 2020)
Cervical spondylotic myelopathy (CSM) is a common disease of the elderly that characterized by gait instability, sensorimotor deficits and etc. Recurrent symptoms including memory loss, poor attention, etc. have also been reported in recent studies. However, these have been rarely investigated in CSM patients. To investigate the cognitive deficits and their correlation with brain functional alterations, we conducted rs-fMRI signal variability. This is a novel indicator in the neuroimaging field for assessing the regional neural activity in CSM patients. Further, to explore the network changes in patients, Functional Connectivity (FC) and graph theory analyses were performed. Compared with the controls, the signal variabilities were significantly lower in the wide-spread brain regions especially at the default mode network (DMN), visual network, and somatosensory network. The altered inferior parietal lobule signal variability positively correlated with the cognitive function level. Moreover, the FC and the global efficiency of DMN increased in patients with CSM and positively correlated with the cognitive function level. According to the study results: (1) the cervical spondylotic myelopathy patients exhibited regional neural impairments, which correlated with the severity of cognitive deficits in the DMN brain regions; (2) the increased FC and global efficiency of DMN can compensate for the regional impairment.